(untitled) (Revista Inclusiones, 2019)
The complication of the technogenic sphere is proceeding at an accelerating pace; therefore, more and more developed technological competencies are required from a subject of activity. The intensification of the technological sphere requires its reflection in the field of professional training of a modern teacher. The purpose of the article is to justify the need to revise the content, as well as the choice of means and methods, of professional training in connection with the formation of a new technological structure in society, based on a continuous change in the nature of production. A set of psychological and pedagogical conditions that ensure the effectiveness of professional training of students is highlighted. The materials of the article can be used by authors and developers of new approaches and concepts in the modernization of the content and technologies of professional training of a modern teacher.